First report of Klebsiella pneumoniae co-producing OXA-181, CTX-M-55, and MCR-8 isolated from the patient with bacteremia - Ge, Haoyu; Qiao, Jie; Xu, Hao; Liu, Ruishan; Chen, Ruyan; Li, Chenyu; Hu, Xinjun; Zhou, Jiawei; Guo, Xiaobing; Zheng, Beiwen (Frontiers in Microbiology, 2022)
The worldwide spread of carbapenem-resistant Enterobacteriaceae (CRE) has led to a major challenge to human health. In this case, colistin is often used to treat the infection caused by CRE. However, the coexistence of genes conferring resistance to carbapenem and colistin is of great concern. In this work, we reported the coexistence of blaOXA-181, blaCTX-M-55, and mcr-8 in an ST273 Klebsiella pneumoniae isolate for the first time. The species identification was performed using MALDI-TOF MS, and the presence of various antimicrobial resistance genes (ARGs) and virulence genes were detected by PCR and whole-genome sequencing. Antimicrobial susceptibility testing showed that K. pneumoniae 5589 was resistant to aztreonam, imipenem, meropenem, ceftriaxone, cefotaxime, ceftazidime, levofloxacin, ciprofloxacin, gentamicin, piperacillin-tazobactam, cefepime, and polymyxin B, but sensitive to amikacin. S1-pulsed-field gel electrophoresis (PFGE) and Southern blotting revealed the mcr-8 gene was carried on a 138kb plasmid with a conserved structure (IS903B-ymoA-inhA-mcr-8-copR-baeS-dgkA-ampC). In addition, blaOXA-181 was found on another 51kb plasmid with a composite transposon flanked by insertion sequence IS26. The in vitro conjugation experiments indicated that the plasmid p5589-OXA-181 and the p5589-mcr-8 were conjugative, which may contribute to the propagation of ARGs. Relevant detection and investigation measures should be taken to control the prevalence of pathogens coharboring blaOXA-181, blaCTX-M-55 and mcr-8.